(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
This article examines the challenges of addressing comprehensive sexual education (ESI) in rural contexts in collaboration with different actors in the educational community: teachers, children and adolescents. To do so, we reconstruct the experience of the university extension project “Comprehensive sexual education for children and teachers in a rural school” in which teachers and students from the Universidad Nacional de Santiago del Estero (UNSE) participated. The project was developed in the Copo department, province of Santiago del Estero, with the organization of the Salado Norte Women’s Front, the Primary School No. 806 El Ceibal and the Secondary School No. 86,063 during the year 2022. From an ethnographic and feminist perspective, experiences in the territory are analyzed. ESI has allowed teachers to change perceptions and prejudices about sexuality, but also for children and adolescents to be able to talk about what happens to them, what they feel and what they want, as well as to reveal painful situations of abuse.